Synthesis and Characterization of LiNi0.7–xMgxCo0.3O2 (0≤x≤0.1) Cathode Materials for Lithium-Ion Batteries Prepared by a Sol-Gel Method - Hailang Zhang (Advances in Materials Science and Engineering)
Prospective cathode materials LiNi0.7–xMgxCo0.3O2 (0≤x≤0.1) for a lithium-ion secondary battery were synthesized using a sol-gel method. The structural and electrochemical properties were examined by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), cyclic voltammetry(CV), and charge-discharge tests. The results show that the LiNi0.7–xMgxCo0.3O2 maintains the α-NaFeO2 type layered structure regardless of the magnesium content in the range x⩽0.1. On the other hand, Mg-doping improves the capacity retention well. Besides, the Mg-doping promotes the diffusion of Li+ in LiNi0.7Co0.3O2. Moreover, Mg-doping suppresses the phase transitions that usually occur in LiNiO2 during cycling and improves the charge-discharge reversibility of Li/LiNi0.7Co0.3O2. High temperature cycling performance of the cathode at 55.5°C is also improved by Mg-doping, which is possibly attributed to the total stronger metal-oxygen bonding and the enhanced structure stability of those delithiated Mg-doped cathodes during cycling.